OPINION: Rokeya’s tolerance and magnanimity - Hasan, Md. Mahmudul (The Daily Star, Dhaka, 2015)
In the current political climate of intolerance and hostility in Bangladesh, religious bigotry and narrow-mindedness in the Indian subcontinent and the brooding atmosphere of prejudice and racism and a steady procession of one war after another globally, Rokeya‟s example of tolerance and magnanimity can be a panacea only if people are ready to heed messages, and follow examples, like hers.